Association of the Polygenic Risk Score With the Probability of Prodromal Parkinson’s Disease in Older Adults - Maraki, Maria I.; Hatzimanolis, Alexandros; Mourtzi, Niki; Stefanis, Leonidas; Yannakoulia, Mary; Kosmidis, Mary H.; Dardiotis, Efthimios; Hadjigeorgiou, Georgios M.; Sakka, Paraskevi; Ramirez, Alfredo; Grenier-Boley, Benjamin; Lambert, Jean-Charles; et al. (Frontiers in Molecular Neuroscience, 2021)
Several studies have investigated the association of the Parkinson’s disease (PD) polygenic risk score (PRS) with several aspects of well-established PD. We sought to evaluate the association of PRS with the prodromal stage of PD. We calculated PRS in a longitudinal sample (n = 1120) of community dwelling individuals ≥ 65 years from the HELIAD (The Hellenic Longitudinal Investigation of Aging and Diet) study in order to evaluate the association of this score with the probability of prodromal PD or any of the established risk and prodromal markers in MDS research criteria, using regression multi-adjusted models. Increases in PRS estimated from GWAS summary statistics’ ninety top SNPS with p < 5 × 10–8 was associated with increased odds of having probable/possible prodromal PD (i.e., ≥ 30% probability, OR = 1.033, 95%CI: 1.009–1.057 p = 0.006). From the prodromal PD risk markers, significant association was found between PRS and global cognitive deficit exclusively (p = 0.003). To our knowledge, our study is the first population based study investigating the association between PRS scores and prodromal markers of Parkinson’s disease. Our results suggest a strong relationship between the accumulation of many common genetic variants, as measured by PRS, and cognitive deficits.